Sexually active older Australian's knowledge of sexually transmitted infections and safer sexual practices - Anthony Lyons; Wendy Heywood; Bianca Fileborn; Victor Minichiello; Catherine Barrett; Graham Brown; Sharron Hinchliff; Sue Malta; Pauline Crameri (Elsevier, 2017)
Abstract Objective: Rates of sexually transmitted infections (STIs) are rising among older Australians. We conducted a large survey of older people's knowledge of STIs and safer sexual practices. Methods: A total of 2,137 Australians aged 60 years and older completed the survey, which included 15 questions assessing knowledge of STIs and safer sexual practices. We examined both levels of knowledge and factors associated with an overall knowledge score. Results: In total, 1,652 respondents reported having sex in the past five years and answered all knowledge questions. This group had good general knowledge but poorer knowledge in areas such as the protection offered by condoms and potential transmission modes for specific STIs. Women had better knowledge than men. Men in their 60s, men with higher education levels, and men who thought they were at risk of STIs reported better knowledge than other men. Knowledge was also better among men and women who had been tested for STIs or reported 'other' sources of knowledge on STIs. Conclusions: Many older Australians lack knowledge of STIs and safer sexual practices. Implications for public health: To reverse current trends toward increasing STI diagnoses in this population, policies and education campaigns aimed at improving knowledge levels may need to be considered.